A SOCIOLOGICAL APPROACH ON KIN MARRIAGES IN TURKEY - Kadir Canatan (Akademik İncelemeler Dergisi)
This paperintends to do a sociological analysis of kin marriage, a subject matter ofsharp discussions both in Turkish society and in European public.Traditionally, to some extent, practiced and largely approved by the society inTurkey, this type of marriage was opened to discussions during the second halfof the last century. The discussions started to be gradually dominated by amedical discourse that focuses on bio-medical results of kin marriage andtreats it as a risk factor. Althoughsuch views are widely accepted in society, kin marriage insistently keeps itsexistence. Based on a sociological perspective, this paper aims to analyze thefactors leading to the existence of kin marriage despite wide spreadingdisapproval thoughts and attitudes against it.